Feature-tailored spectroscopic analysis of the SNRsupernova remnant Puppis A in X-rays - Luna, Gerardo Juan Manuel (2016)
We introduce a distinct method to perform spatially-resolved spectral analysis of astronomical sources with highly structured X-ray emission. The method measures the surface brightness of neighbouring pixels to adaptively size and shape each region, thus the spectra from the bright and faint filamentary structures evident in the broadband images can be extracted. As a test case, we present the spectral analysis of the complete X-ray emitting plasma in the supernova remnant Puppis A observed with XMM-Newton and Chandra. Given the angular size of Puppis A, many pointings with different observational configurations have to be combined, presenting a challenge to any method of spatially-resolved spectroscopy. From the fit of a plane-parallel shocked plasma model we find that temperature, absorption column, ionization time scale, emission measure and elemental abundances of O, Ne, Mg, Si, S and Fe, are smoothly distributed in the remnant. Some regions with overabundances of O-Ne-Mg, previously characterized as ejecta material, were automatically selected by our method, proving the excellent response of the technique. This method is an advantageous tool for the exploitation of archival X-ray data.